Expression of the global regulator SATB1 is an independent factor of poor prognosis in high grade epithelial ovarian cancer - Nodin Björn; Hedner Charlotta; Uhlén Mathias; Jirström Karin (BMC, 2012)
Abstract Background The global gene regulator Special AT-rich sequence-binding protein1 (SATB1) has been reported to reprogramme tumour cells into a more malignant phenotype and associate with poor clinical outcome in several cancer forms. In this study, we investigated the molecular correlates and prognostic impact of SATB1 expression in human epithelial ovarian cancer (EOC). Findings Immunohistochemical expression of SATB1 was examined in tissue microarrays with tumours from 151 incident EOC cases from two prospective, population-based cohorts. Benign-appearing fallopian tube epithelium from 32 cases was also analyzed. A multiplier of nuclear fraction and staining intensity of SATB1 was calculated. While barely expressed in tubal epithelium, nuclear SATB1 expression was denoted in 35/151 (23.2%) EOC cases. Spearman´s Rho test revealed an inverse correlation between SATB1 expression and histological grade (R = -0.22, p = 0.006) and a positive correlation with expression of dachshund 2 protein (R = 0.28, p = 0.001), phosphorylated Chek1 (R = 0.26, p = 0.002) and minichromosome maintenance protein 3 (R = 0.17, p = 0.042). Univariable Cox regression analysis revealed that SATB1 expression, while not prognostic in the full cohort, was associated with a reduced ovarian cancer-specific survival and 5-year overall survival in high grade tumours (n = 105) (HR = 2.14 and HR = 1.96, respectively). This association remained significant in multivariable analysis, adjusted for age and clinical stage (HR = 2.20 and HR = 2.06, respectively). Conclusions These results demonstrate that SATB1 expression is an independent factor of poor prognosis in high grade EOC and correlates in vivo with cellular processes involved in the maintenance of DNA integrity. The functional basis for these observations merits further investigation.